Genes, categories, and species : the evolutionary and cognitive causes of the species problem - Hey, Jody (Oxford University Press, 2001)
In Genes, Categories and Species, Jody Hey provides an enlightening new solution to one of biology's most ironic and perplexing puzzles. When Darwin showed that life evolves, and that it does so by natural selection, he transformed our understanding of living things. But the very question Darwin addressed-the nature of species-continues to pose an awkward conundrum for biologists. Despite enormous efforts by a great many scholars, biologists still cannot agree on how to identify species or even how to define the word "species." Genes, Categories, and Species is not like other books on the spec.
Keywords: Species.; Espèces (Biologie); SCIENCE -- Life Sciences -- Evolution.; Especies.; Species